Os tratados internacionais contra a tortura e o direito penal brasileiro - Albernaz, Flávio Boechat (2007)
The study presented hereunder has as its theme the influences performed by the international treaties against torture crimes in the Brazilian Criminal Law. The very study briefly analyses the main treaties that compose the international system of fundamental rights protection, its historical background and its principles, emphasizing the international treaties against torture made under the United Union UN and the Organization of American States OAS. The core issue of such paper is the study of Brazilian Criminal Law, the influences received by the international treaties over the human rights and it compares that system with the assumed obligations made by Brazil before the international community against torture crime. It concludes that, in general, this country does not obey the former demands accepted in the treaties, especially concerning the criminal punishment. Finally, the dissertation presents the influence of the international treaties of human rights in general, and those against torture specifically, regarding the function developed by the Criminal Law towards society: as a guarantee of ruled expectations established in the international treaties demanding the impartial, serious and thorough investigation of the proceedings and severe punishment of such aggressions to fundamental rights of a human being